Starch structural and functional properties of waxy maize under different temperature regimes at grain formation stage - Xiaotian Gu; Xiaoyu Zhang; Weiping Lu; Dalei Lu (Food Chemistry: X, 2022)
Global warming affects crop productivity, but the influence is uncertain under different temperature regimes. The impact of growth temperatures (T0, 28 °C/20 °C; T1, 32 °C/24 °C; T2, 36 °C/28 °C; T3, 40 °C/32 °C) at grain formation stage on the waxy maize starch physicochemical properties of Suyunuo5 (heat-sensitive hybrid) and Yunuo7 (heat-tolerant hybrid) was studied. Compared with T0, T2 and T3 resulted in a higher number of starch granules with more pitted or uneven surface due to the enhanced enzymatic activities of α-amylase and β-amylase. Meanwhile, large starch granule size, long amylopectin chain-length, and high relative crystallinity under T2 and T3 resulted in low pasting viscosities and gelatinization enthalpy and high retrogradation percentage, especially under T3. The low coefficient variation of gelatinization temperatures indicated that the differences were meaninglessness. The influence of T1 on the pasting viscosities were more obvious in Suyunuo5. In conclusion, high temperatures at grain formation stage deteriorated the starch pasting and retrogradation properties.